Tier-specific contextualised high-intensity running profiles in the English Premier League: more on-ball movement at the top - Ju, Wonwoo; Hawkins, Richard; Doran, Dominic; Gómez-Díaz, Antonio; Martín-García, Andrés; Evans, Mark; Laws, Andy; Bradley, Paul (Biology of Sport, 2023)
The present study aimed to determine the physical-tactical profiles of elite football teams and individual players according to final league rankings. A total of 50 English Premier League matches (n = 100 match and 583 player observations) were analysed by coding the player’s physical-tactical actions through synchronising tracking data and video. Final league rankings were categorised into Tiers: (A) 1st–5th ranking (n = 25), (B) 6th–10th ranking (n = 26), (C) 11th–15th ranking (n = 26), and (D) 16th–20th ranking (n = 23). One-way analyses of variance were used to compare match performances between different Tiers, and effect size (ES) was determined for the meaningfulness of the difference. Tier A teams covered 39–51% more high-intensity distance for ‘Move to Receive/Exploit Space’ (ES: 1.3–1.6, P < 0.01) and ‘Run with Ball’ (ES: 0.9–1.0, P < 0.05) than Tier C and D, and 23–94% more distance for ‘Over/Underlap’ (ES: 1.0, P < 0.01), ‘Run in Behind/Penetrate’ (ES: 0.7, P < 0.05), and ‘Break into Box’ (ES: 0.9, P < 0.05) compared to Tier C. Central and Wide Defensive Players in Tier A covered 65–551% more high-intensity ‘Move to Receive/Exploit Space’ distance compared to other Tiers (ES: 0.6–1.0, P < 0.01). Moreover, the additional options within the physical-tactical actions and zonal differences unveiled more meaningful insights into ‘HOW’ the top Tier teams physically and tactically perform. Thus, the amalgamated physical-tactical data help improve our understanding of a team’s playing style relative to their competitive standard.